Analysis of Operational Standards and Procedures of Murabahah Financing in the Decline of Non-Performing Financings (Case Study PT. Bank Shariah Indonesia Branch of Servant Sukaramai) - Subandi, Subandi; Anggraini, Tuti; Harianto, Budi (Universitas Ibn Khladun Bogor, 2023)
Non-performing financing is a big concern in the banking environment, both conventional and sharia banks. Non-performing financing or has a detrimental effect on the development of the bank. One of the consequences is the non-payment of part or all of the financing. The higher the level of non-performing financing, the worse the liquidity health of the bank, and the lower the level of confidence of depositors who entrust their money. This study aims to determine the analysis of operational standards and procedures for murabahah financing in reducing non-performing financing (Case study of PT. Bank Syariah Indonesia sukaramai sub-branch). The method in this research uses descriptive qualitative, data obtained through interviews with bank employees and data related to the research. The results showed that in reducing non-performing financing at PT Bank Syariah Indonesia Sukaramai Sub-Branch, there are several strategies carried out, namely Reshceduling (rescheduling), Reconditioning (re-requirement), and Execution (confiscation of customer's collateral).